Influence of nano TiO2/Micro (SiC/B4C) Reinforcement on the Mechanical, Wear and Corrosion Behaviour of A356 Metal Matrix Composite - Paulraj, D.; Jeyakumar, P.D.; Rajamurugan, G.; Krishnasamy, P. (Archives of Metallurgy and Materials, 2021)
This work investigates the distribution and the effect of synthesized nano TiO2, micro SiC and B4C particle on the aluminium (A356) metal matrix composites (AMMC). The consequences of this reinforcement on the mechanical, tribology and corrosion behaviour of the AMMC matrix are analyzed. The nano TiO2 is synthesized by wet chemistry sol-gel process, and the reinforcements are added with A-356 by stir casting method. The ASTM standard test specimens are characterized through mechanical, tribology, and corrosion tests for identifying their properties. The metallurgical characterization has been deliberated through XRD and SEM with EDS. In the tensile test results, the percentage of elongation is dropped drastically by 73% due to the enhanced volume % of nano TiO2, micro SiC, and B4C particles. The particle addition of the wear rate and weight loss are reduced at different volume percentages of the A356 matrix. The time plays a significant role in the corrosion rate. The test results also confirm that the corrosion rate is comparatively minimum in 24 hrs (592.35 mm/yr) duration than the 48 hrs (646.368 mm/yr) in both the solutions.
Keywords: Nano TiO2; SiC; B4C; Wear; Corrosion